2020
DOI: 10.1108/jpbm-08-2019-2546
|View full text |Cite
|
Sign up to set email alerts
|

Effect of message orientation/vividness on consumer engagement for travel brands on social networking sites

Abstract: Purpose The purpose of this study is to examine how consumer-brand engagement on social networking sites (SNS) is an outcome of the message orientation/vividness. Design/methodology/approach Message design is proposed to include two components, namely, orientation and vividness. The message orientation is classified as either task/instrumental or socioemotional. The message vividness is measured through content type. The consumer-brand engagement is conceptualized at three levels, namely, cognitive (comment)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 66 publications
3
24
2
2
Order By: Relevance
“…From a behavioral perspective, consumers' involvement in brand-related social media activities is largely accepted as an expression of engagement (Vivek et al, 2012;Yousaf et al, 2020). In these contexts, consumers engage as co-creators of brand messages (Jahn and Kunz, 2012;Iglesias et al, 2019;Guzel et al, 2020;Merrilees, et al 2021), as part of the digital ecosystem (Morgan-Thomas et al, 2020), as contributors in offering their viewpoint, and as followers (Dessart et al, 2015).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…From a behavioral perspective, consumers' involvement in brand-related social media activities is largely accepted as an expression of engagement (Vivek et al, 2012;Yousaf et al, 2020). In these contexts, consumers engage as co-creators of brand messages (Jahn and Kunz, 2012;Iglesias et al, 2019;Guzel et al, 2020;Merrilees, et al 2021), as part of the digital ecosystem (Morgan-Thomas et al, 2020), as contributors in offering their viewpoint, and as followers (Dessart et al, 2015).…”
Section: Conceptual Background and Hypotheses Developmentmentioning
confidence: 99%
“…Functional value reflects the perceived utility of the valuedelivering attributes or characteristics of offerings (Smith and Colgate, 2007). It may involve different types of characteristics: (a) aesthetics, quality, customization or creativity; (b) reliability, performance quality, or service-support outcomes; (c) strategic value, effectiveness, operational benefits and environment benefits (Woodruff, 1997); d) price/value for money; and (e) performance/quality (Sweeney and Soutar, 2001). Emotional value reflects the value perceived as a result of offerings´ ability to "arouse or perpetuate feelings or affective states, such as comfort, security, excitement, romance, passion, fear or guilt" (Smith and Colgate, 2007, p: 8), with types of responses changing according to the context (Smith and Colgate, 2007).…”
Section: Value As An Antecedent To Non-sponsored Brand-related Ugc Usesmentioning
confidence: 99%
“…Previous studies have found that different MGC content features can affect consumer engagement, for example, sharing, commenting and liking (Weiger et al, 2019;Yousaf et al, 2021). For example, remunerative MGC increases consumers' commenting, and informative content increases consumers' sharing of MGC (Chandrasekaran et al, 2019).…”
Section: Engagement With Marketergenerated Contentmentioning
confidence: 97%
“…Previous studies have found that different MGC content features can affect consumer engagement, for example, sharing, commenting and liking (Weiger et al. , 2019; Yousaf et al. , 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…As group members will not process the information via the central route, it will be more efficient to maximise the potential of the peripheral cues to create behaviour change. This can be done by using high quality videos or photos combined with texts and links, as was shown by Yousaf et al (2020).…”
Section: H4 Test: Abilitymentioning
confidence: 99%